Spatial Modeling of the Relationship Between the Social Map and the Level of Educational Development in the Municipalities of the Luján River Basin, Argentina - Montes Galbán, Eloy (2024)
This study aimed to determine the degree of association between the social map (Synthetic Economic-Housing Index—ISEH) and the level of educational development (Synthetic Educational Index—ISE) modeled for the municipalities of the Lujan River basin. The indices were constructed by applying multivariate analysis methods based on Geographic Information Systems (GIS), and the Exploratory Analysis of Spatial Data determined their links using a spatial decision support system (SDSS). The result facilitated the contrast of the proposed hypothesis. In this sense, a theoretical statement and a methodological tool are built from the cartography. The analysis highlights the importance of contextual variables and their incidence on educational development indicators since the spatial perspective provides the bases to support spatial decision-making at the municipal management level.